Sosialisasi Pemahaman E-commerce di Yayasan Al-Kamilah, Serua, Bojongsari, Depok - Shanti Darmastuti; Mansur Juned; Sindy Yulia Putri; Syahrul Salam; Rahmadini Agung Ayu Utami (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The development of internet technology is an interesting thing in the utilization of economic activities. E-commerce is one of the interesting topics that has surfaced in current business activities. Sales and promotion to expand the market is the main goal of using e-commerce. In this regard, the service team conducted e-commerce socialization activities for students at the Yayasan Al-Kamilah to provide participants with a basic understanding of the meaning of e-commerce and its forms. In carrying out the activity, the service team distributed pre-tests which were followed by socialization activities and distribution of post-tests. From the activities carried out, the participants were very enthusiastic about learning more of e-commerce, because the participants only understood about the marketplace. In addition, after the socialization activities, participants also understood the economic benefits of e-commerce.